2019
DOI: 10.3389/fimmu.2019.01396
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Bispecific T-Cell Engager Antibody Targeting the Transferrin Receptor

Abstract: Bispecific T-cell engager antibodies (BiTE) have been explored as a means to recruit cytolytic T cells to kill tumor cells. The transferrin receptor (TfR) is highly expressed on the surface of rapidly proliferating tumor cells. Therefore, it holds great potential in T cell redirecting therapies. In this research, we developed a BiTE targeting TfR and CD3 (TfR-BiTE) and studied its therapeutic impact on TfR-positive cancer. TfR-BiTE had the ability to induce the selective lysis of various TfR-positive cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Many patients with B-cell malignancies have achieved complete remission after receiving CAR T cells targeting the met by many targetable antigens which are shared between normal and malignant T cells, resulting in the mutual killing of CAR T cells to greatly reduce their therapeutic efficacy (38). Our data and previous reports show that the TfR expression on quiescent PBMCs is considerably low (28) but has a certain upregulation on activated T cells. Persis J Amrolia et al also reported that up to 39.3% T cells (basal line 2.6%) upregulated their TfR expression within 3 days of mixed lymphocyte reaction (39), but this figure rose to 65% ± 23% on proliferating alloreactive T cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Many patients with B-cell malignancies have achieved complete remission after receiving CAR T cells targeting the met by many targetable antigens which are shared between normal and malignant T cells, resulting in the mutual killing of CAR T cells to greatly reduce their therapeutic efficacy (38). Our data and previous reports show that the TfR expression on quiescent PBMCs is considerably low (28) but has a certain upregulation on activated T cells. Persis J Amrolia et al also reported that up to 39.3% T cells (basal line 2.6%) upregulated their TfR expression within 3 days of mixed lymphocyte reaction (39), but this figure rose to 65% ± 23% on proliferating alloreactive T cells.…”
Section: Discussionmentioning
confidence: 52%
“…These optimized antibodies exhibited secure and efficacious anti-tumor activity and proved TfR was a worthwhile pharmaceutical target for the development of tumor therapy. With special focus on T cell–redirection strategies for cancer treatment, the anti-TfR mAb has been developed to generate TfR-targeted bispecific T-cell engager antibodies ( 27 ) and the TfR-BiTE was proven to have the ability to induce the selective lysis of various TfR + cancer cells through the activation of T cells ( 28 ), assuring the application of TfR as target for this type of immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this table also includes CD3-BsAb formats based on affinity-enhanced TCR-like domains that recognize peptide–human leukocyte antigen (HLA) complexes (immune mobilizing monoclonal T-cell receptors against cancer (ImmTACs)) [ 42 ]. Multiple other TAAs are currently pursued in preclinical studies hoping to make their way to the clinic, including B7-H4, CD133, CD155, claudin 6 (CLDN6), cellular mesenchymal to epithelial transcription factor (C-MET), ephrin receptor A10 (EphA10), folate receptor 1 (FOLR1), HLA-A*24:survivin 2B 80-88 , integrin β4 (ITGB4), P-cadherin, prolactin receptor (PRLR), receptor tyrosine kinase-like orphan receptor 1 (ROR1), TNF-related apoptosis-inducing ligand receptor (TRAIL-R2), transferrin receptor (TfR) and tumor-associated calcium signal transducer 2 (Trop-2) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Main Textmentioning
confidence: 99%
“…BiTEs are bispecific antibodies which bind to specific tumor antigens on one side, and to the CD3 epsilon chain of the T-cell receptor complex on the other ( 63 , 64 ). This dual interaction enables T cells engagement with tumor cells, which leads to T cell activation, cytolytic synapses, and tumor cell lysis ( 65 , 66 ).…”
Section: Immunotherapy In MMmentioning
confidence: 99%